FOOD INTAKE, PHYSICAL ACTIVITY, AND FASTING BLOOD GLUCOSEAMONG TYPE 2 DIABETES MELLITUS PATIENTS: A CROSS-SECTIONALSTUDY - Rizky Meuthia Pratiwi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder marked by hyperglycemia due to reduced insulin sensitivity and impaired insulin secretion. Poor monitoring of dietary intake and low physical activity often worsen glycemic control. This study aimed to determine the relationship between dietary intake assessed through food recall, physical activity, and fasting blood glucose levels in T2DM patients. This quantitative research employed a descriptive correlational design with a cross-sectional approach and was conducted at Blooto Public Health Center in September 2025. A total of 80 respondents were selected using convenience sampling. Data were collected using a 3-day food recall analyzed with the FatSecret application, the International Physical Activity Questionnaire (IPAQ), and fasting blood glucose measurements using a glucometer. Data analysis included Chi-square tests and Linear Regression. Results showed that 60% of respondents consumed more than 50 grams of sugar per day, 60% had light to moderate physical activity, and 62.5% exhibited elevated fasting blood glucose (>100 mg/dL). Significant relationships were found between food recall and fasting blood glucose (p = 0.000) and between physical activity and fasting blood glucose (p = 0.000). However, the combined effect of dietary intake and physical activity was not significant (p = 0.996). Strengthening dietary education and promoting regular physical activity are essential to improve glycemic control in T2DM patients.